ENHANCING INTERNATIONAL COOPERATION FOR SHIP AND PORT FACILITY SECURITY TO ADDRESS SECURITY DISRUPTIONS - Ubjaan, Mexi Miano; Pramono, Agung; Pramono, Budi (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Port security is a crucial component of maritime security that plays a vital role in facilitating economic activity at sea, particularly in the transit of people, commodities, and services. The terrorist assault on September 11, 2001, commonly referred to as 9/11, resulted in the destruction of the twin towers of the World Trade Centre (WTC) in New York, United States. This event served as the catalyst for the adoption of the International Ships and Port Facility Security Code (ISPS Code) across all port facilities. It is desired that acts of terrorism, narcotics smuggling, illegal drug trafficking, piracy, and theft do not take place. The objective of this study is to examine the execution of security system policies, the compliance of port facility facilities and infrastructure, and the necessary measures to regulate and meet these facilities and infrastructure. The ultimate goal is to reduce and prevent potential security risks to port facilities. Several member countries of the International Maritime Organisation (IMO) are driven to amend the international convention, commonly referred to as the International Ship and Port Facility Security Code (ISPS Code), or the International Code pertaining to the security of ships and port facilities, with the aim of guaranteeing the safety of ships and port facilities.